logx + log(x+1) = log 6 . find x
Answers
Answered by
12
logx + log(x+1) = log6
log[x(x+1)] = log6
x^2 + x = 6
x^2 +x - 6= 0
x^2 + 3x - 2x - 6 =0
x(x+3) - 2(x-3) = 0
(x+3)(x-2) = 0
x = -3
x = 2
Hope it helped you
log[x(x+1)] = log6
x^2 + x = 6
x^2 +x - 6= 0
x^2 + 3x - 2x - 6 =0
x(x+3) - 2(x-3) = 0
(x+3)(x-2) = 0
x = -3
x = 2
Hope it helped you
smileymrinmayipeo48x:
thank you
Answered by
2
i think you know the basic algorithm which is
![log(m) + log(n) = log(mn) log(m) + log(n) = log(mn)](https://tex.z-dn.net/?f=+log%28m%29+%2B+log%28n%29+%3D+log%28mn%29+)
so,
x(x+1)=6
x^2+x-6=0
its your eqn now you can solve it easily
so,
x(x+1)=6
x^2+x-6=0
its your eqn now you can solve it easily
Similar questions
Social Sciences,
8 months ago
Hindi,
8 months ago
Math,
8 months ago
Math,
1 year ago
Economy,
1 year ago
Business Studies,
1 year ago
Physics,
1 year ago